Impact of Premna microphylla Turcz leaf water extracts on the properties of gelatin-carrageenan edible film and its application in cherry tomatoes storage - Ping-Hsiu Huang; Cen-Hao Jian; Yu-Wen Lin; Da-Wei Huang (Food Chemistry: X)
This study investigated the potential of enhancing edible film (EF) formulations by incorporating Premna microphylla Turcz leaf (PM) water extracts (PMWE) and glycerol as plasticizers. Incorporating 75 % PMWE and 5 % glycerol significantly improved the physicochemical and mechanical properties of the films while effectively preserving the quality indicators and extending the shelf-life of cherry tomatoes (CT; Lycopersicon esculentum Mill) in film and coating applications. The PMWE-based films and coatings reduced decay rates (from 80 to 36–52 %) and exhibited a statistically significant difference (p < 0.05) compared to the control group. These findings highlight the potential of PMWE as an effective ingredient in EF formulations, capable of extending shelf-life to 12–16 days, offering promising applications in packaging materials. However, further advancements are required to address the limitations and enable large-scale trials during the mass production stage. Expecting to achieve optimized process formulations and conditions for CT or other agricultural product packaging materials.